Effect of Lutein in Development of Experimental Diabetic Nephropathy in Rats - R.D. Budhiraja, Taruna Katyal, Gurpreet singh (Journal of Pharmaceutical Research and Opinion, 2014)
The present study has been designed to investigate the effect of lutein in streptzotocinÂ  induced diabetic nephropathy in wistar rats. Diabetic nephropathy was induced by administering single dose of streptozotocin in wistar rats. DN was clinically assessed by the estimation of various biochemical parameters and histopathological studies of renal tissue. Diabetic nephropathy was assessed biochemically by blood urea nitrogen, serum creatinine, total urinary protein. Oxidative stress assessed by measuring the TBARS level &renal reduced glutathione levels. Treatment with high dose of lutein (1.5mg/kg, p.o.) shows significant improvement in (BUN, serum creatinine, total urine protein, ratio of kidney wt/body wt, TBARS, reduced glutathione) renal parameters studied for DN. It may be therefore concluded that renoprotective effect of lutein is due to its antioxidant property. Lutein may prevent overproduction of ROS and to increase the removal of preformed ROS This may prove to be effective in preventing the development and progression of diabetic nephropathy.